La réflexivité : exercice pédagogique et outil d'accompagnement aux cycles supérieurs - Andréanne Gélinas Proulx; Anne-Sophie; Lilia A. Simões Forte; Megan Cotnam-Kappel; Caroline Fallu; Lucie Bartosova
The results presented in this paper stem from an exploratory qualitative co-constructed auto-ethnography on reflexivity in graduate students. Reflexivity promotes analytical and critical self-assessment of a person's position, role and professional practices. The purpose of this study is to get a better understanding of the contribution of reflective practice in masters' or doctoral students' development. The data is comprised of self-reflective texts written by six graduate students, namely the authors of this article. A general inductive analysis of the data has highlighted three dimensions related to identity: the person, the student and the novice researcher. The results of the study demonstrate that reflexivity is indeed a beneficial pedagogical exercise and mentoring tool for graduate students.